Ecologia doméstica e transação de conhecimento entre grupos domésticos potiguara da aldeia Jaraguá de Monte-Mór, PB - Araújo, Marianna de Queiroz (2017)
This dissertation aims to describe and analyze the domestic ecology among domestic groups (Wilk, 1984) of Jaraguá de Monte-Mór village, PB, taking into account how people relate to environments in which they are inserted (Silva, 2009). It is also intended to analyze how the transaction of locally constructed knowledge takes place. The theoretical and methodological assumption is the existence of cultural stocks (Barth, 2000), different from social actors (based on age, sex, occupational insertions, etc.), made up of flows of cultural materials (ideas, Knowledge, techniques, etc.) also varied, as we could observe. For its development, data were collected on the activities carried out by the members of two domestic groups (formed by extended families of at least three generations), in which we investigated the material and immaterial aspects of production and transactilon of knowledge, as well as the reference moral frameworks and the cooperation between them. The data show that the individuals interact with the environments when performing activities diversified in their daily life, integrating knowledge, techniques, materials, etc., from their experiential baggage. This procedure occurs with the development of different insertions of people's actions and the uses that they develop, which are fundamental for the identity and experiential conformation of individuals and their domestic groups. From this, it is understood that the interaction with the environments occurs through the knowledge originated not only from the experience in the search for resources, but from a care that generates a relation of responsibility and belonging, a domestic ecology that includes the capacity to deal adequately with the environmental characteristics and to develop the proper management of the elements present in the territory.